Auditoría de Cumplimiento Ambiental a la Estación de Servicios de la Cooperativa de Transportes Loja, período 2022. - Lojan Granda, Stalin Ivan (2024)
The present Curricular Integration Project titled "Environmental Compliance Audit to the Loja Transport Cooperative Service Station, period 2022", intends to determine the degree of environmental compliance at the Loja Transport Cooperative Service Station. It is based on the parameters established in the ISO 1400 Environmental Management System standard, in the period 2022. The project is guided by predefined objectives and employs a mixed approach, specifically a descriptive exploratory type, enabling the collection of essential information and documentation. The planning phase facilitates the definition of objectives, scope, and the audit team. Subsequently, in the execution phase, the environmental compliance audit occurs concurrently with detailed reviews of operational and environmental management procedures. Then, a final audit report is elaborated, highlighting the main findings: the service station lacks maintenance records for every 150 hours of emergency generator operation; there is no record of cleaning regarding the perimeter gutter; evidence of activities conducted is absent; maintenance records are not available; helmets and harnesses are not used by authorized fuel unloading personnel as stipulated in the EMP; there is no record of the use of the first aid kit supplies. Finally, there is no record of informative meetings with the community. Finally, these results are published in the final audit report which includes the respective comments, conclusions and recommendations in order to ensure that they are implemented to improve the proper functioning of the service station in environmental terms.